Willingness to pay for outpatient services user fees: Malaysian community perspective - Azimatun Noor Aizuddin,; Syed Mohamed Al Junid, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Health care services are not often accessible and available for all people in one country due to multiple reasons such as the geographical barrier, affordability, etc. The aim of this study was to analyse willingness to pay (WTP) for healthcare services user fees among Malaysian population and determine its’ influencing factors. Structured interviews were conducted involving 774 households in 4 states represents Peninsular Malaysia. Validated questionnaires with open ended, followed by bidding games were applied to elicit maximum amount of WTP. The study was analysed descriptively and with multivariate regression method to adjust for potential confounding factors. More than half of respondents WTP more than current fee for the government clinic outpatient registration fee with mean MYR3.76 (SD2.71). Majority of respondents not WTP more than usual for private clinic simple outpatient treatment charges with the mean MYR38.76 (SD5.45). Factors that were found to have significant associations with WTP for both government and private clinic were income and having health insurance. Community willing to pay for healthcare services user fees and charges but at certain amount. The healthcare services user fees and charges can be increased up to community WTP level to avoid from catastrophic expenditure.